4 - The Remote Causes of the Oil Workers’ 1994 Strike in Nigeria: 10.4314/ad.v26i2.22143 - Onveonoru , Ifeanvi; Aborisade , Femi (Africa Development, 2001)
Much of what was presented to the Nigerian public and the international community regarding the 1994 oil workers' strike in Nigeria centred on government propaganda - mainly the illegality of the strike and its alleged subversive character. The paper examines the remote causes of the strike — traceable to long-standing deep-seated grievances some of which transcended the internal state of the workplace though central to production. This included the socio-economic deprivations and marginalization suffered by the oil-producing areas in Nigeria. The paper indicates how workplace issues are invariably interwoven with the social, economic and the political spheres and therefore argues that the critical issues that gave the strike its essential character emanated from the social and economic spheres - critical governance issues that cannot be explained simply by 'political motivation'.